Chemical and sensory characteristics of «Arbequina» olive oil obtained in different growing areas of Spain - J. Touss; A. Romero; J. Plana; L. Guerrero; I. Díaz; J. F. Hermoso (Grasas y Aceites, 1997)
Within the quality virgin olive oils produced in Spain, Catalonia has two of the six currently existing Origin Denominations (Garrigues and Siurana). Their production of extra virgin oil proceeds of the «Arbequina» cultivar, approximately 8.000 tm, distributed between the CD «Garrigues», in Lleida (5.000 tm), and «Siurana» in Tarragona (3.000 tm). These oils are very appreciated at domestic as well as at international level because of their excellent taste. In the last years, this variety is being expanded in other regions of Spain (Andalusia, Aragon, etc.) and over the worid (Argentina, France, etc.). The physico-chemical and sensory characteristics of «Arbequina» virgin olive oils produced are studied, mainly in Catalonia, Andalusia and Aragon. The obtained preliminary results indicate that some quality parameters of the «Arbequina» oil are variable, being cultivated in different environments, mainly certain fatty acids, polyphenols, oxidative stability and some sensory attributes of the oil.